Recruit, train and evaluate human capital : A case study in Google - Navaratnam Vejaratnam; Tan, Say Peng; Habibah @ Artini Ramlie; Norshahrul Marzuki Mohd Nor; Emy Harlina; Theepa Paramsivam; Shri Dayalam James (The Publisher, 2022)
The unpredictable developments in the environment raised the company's awareness of require human resource managers to create and execute a strategic such as human resource management strategy and practises, business strategies, and the development of a mission and vision for human resource management. In this conceptual study, will evaluate integration of human resource functions with business strategy. A good recruiting strategy is critical for an organization's human capital competitiveness. Furthermore, the training system must be comprehensive, with the goal of assisting the business in achieving even more. In addition, a well-integrated performance management system will contribute to the development of a pleasant employee-employee relationship. Finally, balancing work and life has become critical to an organization's success. Appropriate alignment of human resource management techniques with business strategy allows organisations to fulfil their purpose and vision in the long term, resulting in a competitive edge in markets and the attainment of business objectives